Magnetotail reconnection onset caused by electron kinetics with a strong external driver - San Lu (Nature Portfolio, 2020)
Magnetotail reconnection plays a crucial role in explosive energy conversion in geospace. Here, the authors show that magnetotail reconnection starts from electron reconnection in the presence of a strong external driver, which then develops into ion reconnection.